Sclerostin Antibody Mitigates Estrogen Deficiency-Inducted Marrow Lipid Accumulation Assessed by Proton MR Spectroscopy - Li, Shaojun; Huang, Bingcang; Jiang, Bo; Gu, Mingjun; Yang, Xiaodan; Yin, Ying (Frontiers in Endocrinology, 2019)
Sclerostin knock-out mice or sclerostin antibody (Scl-Ab) treated wild-type mice displayed decreased marrow adiposity. But the effects of Scl-Ab on estrogen deficiency-induced marrow fat expansion remain elusive. In this work, forty-five female New Zealand rabbits were equally divided into sham-operation, ovariectomy controls and ovariectomy treated with Scl-Ab for 5 months. MR spectroscopy was performed to longitudinally assess marrow fat fraction at baseline conditions, 2.5 and 5 months post-operatively, respectively. We evaluated bone mineral density (BMD), bone structural parameters, serum bone biomarkers, and quantitative parameters of marrow adipocytes. Ovariectomized rabbits markedly exhibited expansion of marrow fat in a time-dependent manner, with a variation of marrow fat fraction (+17.8%) at 2.5 months relative to baseline and it was maintained until 5 months (+30.4%, all P < 0.001), which was accompanied by diminished BMD and deterioration of trabecular microstructure. Compared to sham controls, adipocyte mean diameter, adipocyte density and adipocytes area percentage was increased by 42.9%, 68.3% and 108.6% in ovariectomized rabbits, respectively. Scl-Ab treatment increased serum bone formation marker and alleviated the ovariectomy escalation of serum bone resorption marker. It remarkably lessened the ovariectomy-mediated deterioration of BMD, and morphometric characteristics of trabecular bone. Marrow fat fraction was decreased significantly with Scl-Ab to levels matching that of sham-operated controls and correlated positively with reductions in adipocyte mean diameter, percentage adipocyte volume per marrow volume and adipocyte density. Taken together, early Scl-Ab treatment reverts marrow fat expansion seen in ovariectomized rabbits in addition to having a beneficial effect on bone mass and microstructural properties.